Global Superconvergences of the Domain Decomposition Methods with Nonmatching Grids (Journal of Computational Mathematics, 2001)
In this paper, the global superconvergences of the domain decomposition methods with Lagrangian multiplier and nonmatching grids are proven for solving the second order elliptic boundary value problems. Moreover, $L^∞$ and $L^2$ error estimates are discussed and a defect correction scheme is presented.